Centre for Land Tenure Studies 2019 Annual Report - Norwegian University of Life Sciences (NMBU) - Centre for Land Tenure Studies (CLTS) (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2020)
In the year 2019, the Centre for Land Tenure Studies (CLTS) has produced 9 working papers. These papers were circulated on both the CLTS webpage and the Scandinavian Working Papers in Economics (S-WoPEc) webpage. The papers are also available online on the library (Brage) of Norwegian University of Life Sciences (NMBU). Through these webpages, the number of abstract views for the working papers doubled while full paper downloads increased by 11 percent compared to publications in 2018. In the year, CLTS also registered several papers published in international journals through the research work of NMBU faculty members and PhD students. An overview of the activities from faculties at NMBU involved in CLTS research-related work indicates that three PhD students completed their studies while new PhD students were recruited under different research projects in 2019.
Keywords: 330